Impact of biochar application on nitrogen nutrition of rice, greenhouse-gas emissions and soil organic carbon dynamics in two paddy soils of China - Xie, Zubin; Xu, Yanping; Liu, Gang; Liu, Qi; Zhu, Jianguo; Tu, Cong; Amonette, James E.; Cadisch, Georg; Yong, Jean W. H.; Hu, Shuijin (Plant and soil, 2013)
Aims Two field microcosm experiments and ¹⁵N labeling techniques were used to investigate the effects of biochar addition on rice N nutrition and GHG emissions in an Inceptisol and an Ultisol. Methods Biochar N bioavailability and effect of biochar on fertilizer nitrogen-use efficiency (NUE) were studied by ¹⁵N-enriched wheat biochar (7.8803 atom% ¹⁵N) and fertilizer urea (5.0026 atom% ¹⁵N) (Experiment I). Corn biochar and corn stalks were applied at 12 Mgha⁻¹ to study their effects on GHG emissions (Experiment II). Results Biochar had no significant impact on rice production and less than 2 % of the biochar N was available to plants in the first season. Biochar addition increased soil C and N contents and decreased urea NUE. Seasonal cumulative CH₄ emissions with biochar were similar to the controls, but significantly lower than the local practice of straw amendment. N₂O emissions with biochar were similar to the control in the acidic Ultisol, but significantly higher in the slightly alkaline Inceptisol. Carbon-balance calculations found no major losses of biochar-C. Conclusion Low bio-availability of biochar N did not make a significantly impact on rice production or N nutrition during the first year. Replacement of straw amendments with biochar could decrease CH₄ emissions and increase SOC stocks.